2020
DOI: 10.21014/acta_imeko.v9i5.985
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of pressure-induced cavity deformation – the 18SIB04 Quantumpascal EMPIR project

Abstract: The 18SIB04 QuantumPascal EMPIR project aims for development of photon-based standards that can replace primary standards of the SI unit of pressure, the Pascal. In this project, four partners simulated the pressure-induced deformation of a given Fabry-Pérot cavity, using various versions of two types of software, COMSOL Multiphysics (R) and ANSYS Workbench. It was demonstrated that, for a given geometry and set of material parameters, simulations of the deformation could be performed by the various partners w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…In [1] the results of simulating the deformation of the Fabry-Perot cavity are shown, and they are collected in Table 4. The result simulated in Solid Edge software by the CEM is less than 10 -3 time bigger than the average of [1].…”
Section: Comparison With Results From [1]mentioning
confidence: 99%
See 3 more Smart Citations
“…In [1] the results of simulating the deformation of the Fabry-Perot cavity are shown, and they are collected in Table 4. The result simulated in Solid Edge software by the CEM is less than 10 -3 time bigger than the average of [1].…”
Section: Comparison With Results From [1]mentioning
confidence: 99%
“…In [1] the results of simulating the deformation of the Fabry-Perot cavity are shown, and they are collected in Table 4. The result simulated in Solid Edge software by the CEM is less than 10 -3 time bigger than the average of [1]. The uncertainty in CEM's simulation was calculated as a rectangular distribution centred in -6.3846 × 10 -12 Pa -1 and with a width equal to two times the difference of CEM's value and the average value of [1] (2.24 × 10 -14 Pa -1 ).…”
Section: Comparison With Results From [1]mentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate whether Zerodur is more suitable than the ULE glass, different studies are being made, such as the one reported in reference [8]. This evaluation requires the modelling of gas transport dynamics in the material.…”
Section: Introductionmentioning
confidence: 99%